Burnout syndrome in nursing personnel of a referral hospital in Ibague, Colombia, 2014 (2016)
ABSTRACT: Objective: To determine the prevalence of the burnout syndrome (BS) in nursing personnel of a referral hospital in a Colombian city and their relation with demographic variables. Materials and methods: a cross-sectional study was carried out on a random sample representative of 174 female and male nurses stratified based on if the nurse was a professional nurse or a nursing assistant in a referral hospital in the city of Ibague, Colombia. The MBI (Maslach Burnout Inventory) scale was used validated in Colombia. Tests of independence t were used for average differences and a one- way variance analysis. In the multivariate analysis, an explanatory binary logistic regression model was built with a measure of association; the OR is accompanied by its respective 95% confidence interval. Results: The prevalence of the Burnout Syndrome was 20.1% (IC 95%: 13.9 26.4), and 52.3% are at risk of suffering from Burnout Syndrome, they were Nursing professionals who had a temporary job or who were supernumeraries, and personnel who worked in services including administration, oncology, orderlies and sterilization. Men and personnel who stated having more than one contract were the people who presented the highest Burnout indicator ratio of 20.1%. In the multivariate analysis, joint factors which perhaps have greater incidence in the presence of Burnout Syndrome include the number of children and the fact of being a man.Conclusions: In comparison with other studies, this study reveals that the prevalence of the burnout syndrome in a referral hospital is greater.